Principles and properties of ion flow in P2X receptors - Samways, Damien S.; Li, Zhiyuan; Egan, Terrance M. (Frontiers in Cellular Neuroscience, 2014)
P2X receptors are a family of trimeric ion channels that are gated by extracellular adenosine 5’-triphosphate (ATP). These receptors have long been a subject of intense research interest by virtue of their vital role in mediating the rapid and direct effects of extracellular ATP on membrane potential and intracellular Ca2+ concentration, which in turn underpin the ability of ATP to regulate a diverse range of clinically significant physiological functions, including cardiovascular function, pain, and the immune response. An important aspect of an ion channel’s function is, of course, the means by which it transports ions across the biological membrane. A concerted effort by investigators over the last two decades has culminated in significant advances in our understanding of how P2X receptors conduct the inward flux of Na+ and Ca2+ in response to binding by ATP. However, this work has relied heavily on results from current recordings of P2X receptors altered by site-directed mutagenesis. In the absence of a 3-dimensional channel structure, this prior work provided only a vague and indirect appreciation of the relationship between structure, ion selectivity and flux. The recent publication of the crystal structures for both the closed and open channel conformations of the zebrafish P2X4 receptor has thus proved a significant boon, and has provided an important opportunity to overview the amassed functional data in the context of a working 3-dimensional model of a P2X receptor. In this paper, we will attempt to reconcile the existing functional data regarding ion permeation through P2X receptors with the available crystal structure data, highlighting areas of concordance and discordance as appropriate.